2022
DOI: 10.1101/2022.12.20.22283699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promoting Activity, Independence and Stability in early dementia and mild cognitive impairment (PrAISED): A randomised controlled trial

Abstract: Background: Dementia is associated with frailty leading to increased risks of falls and hospitalisations. Interventions are required to maintain functional ability, strength and balance. Design: Multi-centre parallel group randomised controlled trial, with embedded process evaluation. Procedures were adapted during the COVID-19 pandemic. Participants: People with mild dementia or mild cognitive impairment (MCI), living at home, and a family member or carer. Objectives: To determine the effectiveness of an exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Participants recorded exercise on a monthly calendar and reported undertaking a mean of 121 minutes/week of PrAISED exercise. The RCT showed no measurable benefits in ADL, increased physical activity, quality of life or any other of the battery of health status measures studied [13].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Participants recorded exercise on a monthly calendar and reported undertaking a mean of 121 minutes/week of PrAISED exercise. The RCT showed no measurable benefits in ADL, increased physical activity, quality of life or any other of the battery of health status measures studied [13].…”
Section: Introductionmentioning
confidence: 79%
“…The PrAISED RCT found that after 12 months, the Disability Assessment for Dementia (DAD) [21], and a range of other health status measures including balance, activity and quality of life were no different between intervention and control groups [13]. The aims of the process evaluation were to investigate the reception of the programme and explain findings from the RCT by identifying mechanisms, facilitators and barriers to achieving positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The study design for the PrAISED multi-center RCT has been previously reported, covering details such as the randomization method, sample size calculation, participant selection criteria, informed consent, and content of baseline and follow-up questionnaires. 12 …”
Section: Methodsmentioning
confidence: 99%
“…PrAISED (promoting activity, independence, and stability in early dementia) was a multi-center, pragmatic, randomized controlled trial (RCT), which was conducted between October 2018 and September 2022. 12 , 13 Patient participants were recruited from 5 locations in England and were randomized to a control group (usual care) or an intervention group (PrAISED). The intervention was a specifically designed rehabilitation program that provided a home-based exercise program along with promoting access to community activities for people with early dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation